From Past to Present: Philosophical Reflections on AI with a SWOT Approach - Şeyma Bozkurt Uzan (Felsefe Dünyası)
Artificial intelligence (AI) has become a transformative force in the technological world, reshaping various aspects of human life and raising profound philosophical questions. This article explores the intersection of AI and philosophy by conducting a comprehensive literature review and SWOT analysis of 20 significant articles. The study aims to understand how AI influences philosophical debates on ethics, consciousness, intelligence, and human nature. The findings reveal key strengths, weaknesses, opportunities, and threats associated with the current literature. Notable strengths include the foundational impact of highly cited works and the diverse range of topics covered. However, some articles face limitations due to outdated theories or limited practical integration. The study underscores the need for ethical frameworks in AI development and highlights areas for future research, particularly in addressing social justice and equity. By synthesizing existing knowledge, this paper offers new insights into the ethical, social, and philosophical dimensions of AI, providing a solid foundation for future research and policy development.